2013
DOI: 10.1017/jfm.2013.486
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of new three-dimensional modes in the wake of a rotating cylinder

Abstract: A recent numerical study by Rao et al. (J. Fluid Mech., vol. 717, 2013, pp. 1–29) predicted the existence of several previously unobserved linearly unstable three-dimensional modes in the wake of a spinning cylinder in cross-flow. While linear stability analysis suggests that some of these modes exist for relatively limited ranges of Reynolds numbers and rotation rates, this may not be true for fully developed nonlinear wakes. In the current paper, we present the results of water channel experiments on a rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 48 publications
11
31
0
Order By: Relevance
“…This has been seen in rotating cylinder wakes previously, e.g. figure 5 from Radi et al (2013). This is consistent with rotation causing the two separation points, which feed the shed vortices, to move together, thereby restricting the vorticity shed into each wake vortex and increasing cross-annihilation.…”
Section: Wake Structuressupporting
confidence: 86%
“…This has been seen in rotating cylinder wakes previously, e.g. figure 5 from Radi et al (2013). This is consistent with rotation causing the two separation points, which feed the shed vortices, to move together, thereby restricting the vorticity shed into each wake vortex and increasing cross-annihilation.…”
Section: Wake Structuressupporting
confidence: 86%
“…For gap heights G=D≲0:22, mode E is the first three-dimensional mode to become unstable and this occurs for a steady base flow. While this mode was previously observed in the studies of rotating cylinders near a wall (Stewart et al, 2010;Rao et al, 2011Rao et al, , 2013dHourigan et al, 2013), the nomenclature used here is borrowed from studies of an isolated rotating cylinder (Rao et al, 2013a(Rao et al, ,b, 2015aRadi et al, 2013), given the perturbation field of mode E from those studies bears a strong similarity (also see section 3.6, Figs. 6 and 7 of Rao et al, 2013d).…”
Section: Three-dimensional Flowmentioning
confidence: 90%
“…At higher rotation rates, the flow becomes increasingly unstable to perturbations at Re = 200 in the range 3 α 5 (Meena et al 2011). Recent numerical and experimental investigations (Mittal & Kumar 2003;Rao et al 2013b,a;Radi et al 2013) have identified several new three-dimensional transitions for Re < 400. In the Mode I shedding regime, five three-dimensional modes were found to become unstable and, in the steady regime of flow α 2, four three-dimensional modes were observed.…”
Section: Introductionmentioning
confidence: 97%